2009
DOI: 10.1128/aem.01830-08
|View full text |Cite
|
Sign up to set email alerts
|

Community-Level Analysis of psbA Gene Sequences and Irgarol Tolerance in Marine Periphyton

Abstract: This study analyzes psbA gene sequences, predicted D1 protein sequences, species relative abundance, and pollution-induced community tolerance in marine periphyton communities exposed to the antifouling compound Irgarol 1051. The mechanism of action of Irgarol is the inhibition of photosynthetic electron transport at photosystem II by binding to the D1 protein. The metagenome of the communities was used to produce clone libraries containing fragments of the psbA gene encoding the D1 protein. Community toleranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 115 publications
4
31
0
Order By: Relevance
“…It was demonstrated that PSII inhibitor resistance was mainly due to a mutation in the gene sequence coding for the D1 protein (Erickson et al, 1989;Oettmeier, 1999). However, according to the literature available, such mutations were not involved in resistance to irgarol (Eriksson et al, 2009). Cells resistant to contaminants arise randomly by rare spontaneous pre-selective mutation during replication L opez-Rodas et al, 2001).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…It was demonstrated that PSII inhibitor resistance was mainly due to a mutation in the gene sequence coding for the D1 protein (Erickson et al, 1989;Oettmeier, 1999). However, according to the literature available, such mutations were not involved in resistance to irgarol (Eriksson et al, 2009). Cells resistant to contaminants arise randomly by rare spontaneous pre-selective mutation during replication L opez-Rodas et al, 2001).…”
Section: Introductionmentioning
confidence: 92%
“…Recently, tolerance to irgarol in marine periphyton was found to be based not on amino acid substitution, but rather on increased D1 degradation (Eriksson et al, 2009). This latter mechanism seems to be linked to the non-conserved amino acid region (PEST region) involved in regulating D1 protein degradation.…”
Section: Psba Gene Mutation: Resistance To Diuron and Comparison Withmentioning
confidence: 98%
“…8). Evolution of increased tolerance to contaminants is also demonstrated in natural populations of coastal waters (Wirgin and Waldman 2004;Eriksson et al 2009). Moreover, populations of marine organisms sometimes show lower genetic variation at contaminated sites compared to control sites (Ma et al 2000;Bickham et al 2000).…”
Section: Rapid Evolution Of Baltic Sea Populationsmentioning
confidence: 99%
“…Prometryn-exposed communities showed 50% less biomass than controls, reflecting the diminished photosynthetic rate. To survive in a polluted environment, species must develop tolerance mechanisms such as increased detoxification of compounds or alterations of the target site, for example the D1 protein (Eriksson et al 2009). We found shifts not only in the species composition, but also in an enhanced abundance of cyanobacteria on the level of algal classes, which might indicate sensitivity differences in both structural levels.…”
Section: R E S P O N S E T O T O X I C a N T -I N D U C E D S T R E S Smentioning
confidence: 99%